Multi-objective optimization of quarter car passive suspension design in the frequency domain based on PSO. Issue 5 (4th July 2016) - Gomes, Herbert Martins
Abstract : Purpose: – The purpose of this paper is to investigate the optimum design of a quarter car passive suspension system using a particle swarm optimization algorithm in order to minimize the applied loads and vibrations. Design/methodology/approach: – The road excitation is assumed as zero-mean random field and modeled by single-sided power spectral density (PSD) based on international standard ISO 8608. The variance of sprung mass displacements and variance of dynamic applied load are evaluated by PSD functions and used as cost function for the optimization. Findings: – The advantages in using this methodology are emphasized by an example of the multi-objective optimization design of suspension parameters and the results are compared with values reported in the literature and other gradient based and heuristic algorithms. The paper shows that the algorithm effectively leads to reliable results for suspension parameters with low computational effort. Research limitations/implications: – The procedure is applied to a quarter car passive suspension design. Practical implications: – The proposed procedure implies substantial time savings due to frequency domain analysis. Social implications: – The paper proposes a procedure that allows complex optimization designs to be feasible and cost effective. Originality/value: – The design optimization is performed in the frequency domain taking into account standard defined road profiles PSD without the need to simulate in the time domain.